1974
DOI: 10.1111/j.1423-0410.1974.tb02731.x
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of Irregular Red Cell Antibodies and Their Significance in Blood Transfusion and Antenatal Care

Abstract: Abstract. The antibodies encountered in random collectives of 55,350 recipients, 16,643 pregnant women, and 1,307 mothers of babies with hemolytic disease are listed. Antibody screening was performed in all specimens using the same technique (albumin‐antiglobulin test), a limited number of selected sera was investigated also by the auto‐analyzer. Different frequencies of the antibodies concerned were found in all groups. Anti‐Kell was detected in 10% of all antibodies found in recipients whereas the frequency… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

6
29
0
2

Year Published

1982
1982
2016
2016

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(37 citation statements)
references
References 8 publications
(2 reference statements)
6
29
0
2
Order By: Relevance
“…Our results revealed that antibody prevalence in military veterans in a VA hospital setting was 2.4 percent, which was as high or higher than that reported in retrospective studies of other general hospital-based, patient populations. 1,3,4 It is notable that military veterans in our study had this relatively high rate of alloimmunization despite the fact that they were overwhelmingly male; other studies have examined mixed-sex populations. This is an important distinction because women appear more likely to make blood group antibodies than men as a result of antigen exposure during pregnancy and because they appear to have an increased tendency to make naturally occurring blood group antibodies.…”
Section: Discussionmentioning
confidence: 90%
See 3 more Smart Citations
“…Our results revealed that antibody prevalence in military veterans in a VA hospital setting was 2.4 percent, which was as high or higher than that reported in retrospective studies of other general hospital-based, patient populations. 1,3,4 It is notable that military veterans in our study had this relatively high rate of alloimmunization despite the fact that they were overwhelmingly male; other studies have examined mixed-sex populations. This is an important distinction because women appear more likely to make blood group antibodies than men as a result of antigen exposure during pregnancy and because they appear to have an increased tendency to make naturally occurring blood group antibodies.…”
Section: Discussionmentioning
confidence: 90%
“…This is an important distinction because women appear more likely to make blood group antibodies than men as a result of antigen exposure during pregnancy and because they appear to have an increased tendency to make naturally occurring blood group antibodies. 2,4 With regard to RBC alloantibody prevalence in male veterans, it was unclear to what extent the absence of pregnancy-related antibodies might be counterbalanced by the veterans' increased risk of transfusion due to combat-related trauma. Military transfusions during World War II, the Korean War (1950 to 1953), and the Vietnam War (1965 to 1971) accounted for the administration of more than 1.5 million units of blood products to American soldiers.…”
Section: Discussionmentioning
confidence: 98%
See 2 more Smart Citations
“…The overall incidence of alloimmunization in this group is reported to range from slightly less than 1% up to about 3% of patients undergoing type-and-screen testing [6,7,8,9,10,11]. It is important to note that these data arise primarily from retrospective analyses of patients at single institutions undergoing transfusion service antibody screening.…”
Section: Incidence Of Minor Rbc Antigen Alloimmunization In Various Cmentioning
confidence: 99%